Tespa1 regulates T cell receptor-induced calcium signals by recruiting inositol 1,4,5-trisphosphate receptors - Jingjing Liang (Nature Portfolio, 2017)
The thymocyte development protein Tespa1 is known to translate T cell receptor signals by affecting the calcium signalling cascade, but it is not clear how. Here the authors show that Tespa1 recruits IP3R1 to the TCR signalling complex.